PERCEPTION OF DIGNITY AMONGST PATIENTS: AN EMPIRICAL APPROACH - Dr. Vidhi Sharma, Major Navjeet Kaur, Dr. Harminder Kaur Gujral (International Journal of Advanced Science and Technology, 2020)
Health care workers are responsible for providing care to the patients with dignity. There are vulnerable chances of loss of dignity of patients during hospitalization. The purpose of the present research is to study the perception of patients towards their dignity during hospitalization. The study has been conceptualized on demographical variables and the factors contributing in patients’ perception towards their dignity. A sample of ninety-eight patients was randomly taken for the study and SPSS was used to analyse the obtained data. The findings reflect that the gender does not play role but other factors like age, marital status, basic qualification and number of days of hospitalization play an important role in the perception of patients for their dignity. The effect of these demographical variables was studied on the cognitive and behavioural factors like privacy, feeling of left abandoned, recognition, awareness, consent, respect, selfcare, confidentiality, hygiene and culture of patients which play an important role in the perception of patients for their dignity. The implication of the study would be that medical and para-medical staff should be sensitized towards needs of the patients and required training can be provided for quality care of the patients so that their dignity and self-esteem are maintained during hospitalization that would help in further rehabilitation.